Three-dimensional surface contouring of macroscopic objects by means of phase-difference images (2006)
We report a technique to determine the 3D contour of objects with dimensions of at least 4 orders of magnitude larger than the illumination optical wavelength. Our proposal is based on the numerical reconstruction of the optical wave ﬁeld of digitally recorded holograms. The required modulo 2 phase map in any contouring process is obtained by means of the direct subtraction of two phase-contrast images under different illumination angles to create a phase-difference image of a still object. Obtaining the phase-difference images is only possible by using the capability of numerical reconstruction of the complex optical ﬁeld provided by digital holography. This unique characteristic leads us to a robust, reliable, and fast procedure that requires only two images. A theoretical analysis of the contouring system is shown, with veriﬁcation by means of numerical and experimental results. © 2006 Optical Society of America